AN EVALUATION OF THE ABU BAKAR MOSQUE IN BANGSAR FROM THE PERSPECTIVE OF ARCHITECTURAL CONTEXTUALISM AND SOCIAL INCLUSION - KANESH, KEVIN; M. RASDI, MOHD TAJUDDIN; JEAN, LOW MEI; AL-DARAH, HOMAM (Human Sustainability Procedia, 2018)
This research identifies the issues related to the contextualism of mosque architecture towards its urban setting as well as how it translates into inclusivism into the social structure. The social structure comprises of the mosque congregation, community and management as well as its entailing connection to the direct community surrounding the mosque, in more important terms, the Muslim and non-Muslim community. The resulting findings will allow for an understanding on the role that the mosque plays within its community and the implications of its contextualism within the urban fabric.Keywords: Mosque architecture, Contextualism, Social, Urban, Non-Muslim, Muslim